Kesiapan Guru dalam Menghadapi Program Full Day School - Dina Liana (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2020)
The research is to discover the teacher’s readiness on applying full day school program declared by the government. Qualitative research method is used to grow descriptive data in for of interview. The findings clarifies that SMA N 1 Reteh is well-organized in applying full day school program to develop students’ potential by serving meaningful activities, in order to create generation of full of competency, attractiveness, and able to compete in the worldwide, as the 2013 curriculum persistence – building character education.